2014
DOI: 10.1139/cjpp-2014-0066
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity induces an inflammatory response in the common carotid artery of rats

Abstract: Post-spaceflight orthostatic intolerance is one of the most important adverse effects after exposure to space microgravity, and there are still no effective countermeasures. It has been considered that arterial remodeling may play an important role in the occurrence of post-spaceflight orthostatic intolerance, but the cellular mechanisms remain unknown. In this study, we investigated whether an inflammatory response exists in the common carotid artery of rats exposed to simulated microgravity. For this, Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We limited our statistical analyses to five parameters, including traditional risk factors (SBP, total cholesterol, and LDL) (65), a biomarker of inflammation (hs-CRP), and a biomarker of oxidative stress (oxidized LDL). cIMT is thicker during active bouts of rheumatoid arthritis (79), and biomarkers of inflammation are elevated in the carotid artery of rats that experience carotid artery thickening during hindlimb suspension (50). Of the biomarkers we examined, only hs-CRP had a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We limited our statistical analyses to five parameters, including traditional risk factors (SBP, total cholesterol, and LDL) (65), a biomarker of inflammation (hs-CRP), and a biomarker of oxidative stress (oxidized LDL). cIMT is thicker during active bouts of rheumatoid arthritis (79), and biomarkers of inflammation are elevated in the carotid artery of rats that experience carotid artery thickening during hindlimb suspension (50). Of the biomarkers we examined, only hs-CRP had a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The signals were detected using the Super Signal West substrate (Thermo Fisher Scientific, USA). Densitometry analyses of the western bands were performed using the Tanon Imaging software 67 .…”
Section: Methodsmentioning
confidence: 99%
“…Ground-based simulated microgravity studies in HU rats and bed-resting humans have also revealed hypertrophy and increased vasoconstriction of the carotid artery (Hughson et al 2016;Zhang 2013). The mechanisms underlying the changes in artery function and structure may be related to the local renin-angiotensin system, endothelial nitric oxide synthase, ion channels, ras homolog family member A (Rho)/Rho kinase (ROCK), oxidative stress and inflammation (Liu et al 2014;Gao et al 2012;Ren et al 2011;Wu et al 2019;Zhang et al 2020b); however, clear evidence of arterial remodeling requires further exploration.…”
Section: Discussionmentioning
confidence: 99%